The Potential Use of Polymeric Nanomaterials Against the Spread of the SARS-Cov-2 and its Variants: A Necessary Briefing - Corrêa, Harrison Lourenço (Journal of Research Updates in Polymer Science, 2023)
Regarding its evolutionary scale, mankind has made important achievements in a short period of time. The last 50 years have been fundamental for the development of technologies that currently allow human beings to make safe journeys in the orbit of the planet, study and accurately analyze the universe, build smart cities, propose more sustainable production processes, etc. The technological leap of the last decades has influenced practically all sectors, from engineering to medicine. There are many factors that allowed for technological evolution, and one of them refers to the development of new materials. Herein, polymers stand out. The versatility of these materials reinforced their relevance during the SARS-CoV-2 period. In the period when many medical and hospital supplies were exhausted, polymers were useful for manufacturing items such as face shields, general purpose masks, and swabs, helping to counter the spread of the virus. Two years after the pandemic peak, the challenge is to fight the viral variants and make the methods of diagnosis and treatment more effective. In this regard, nanotechnology and nanoscience seem to be promising for this purpose. Through a review study, the present work aims to identify technologies already available or under development that allow for the use of polymeric nanomaterials against the spread of the new coronavirus and its variants.